Behavioral techniques to optimize success of in-office pediatric tympanostomy tube placement without sedation. Issue 12 (December 2015) - Cohen, L.L.; Martin, S.R.; Gamwell, K.L.; McCarty, C.; Shih, S.W.
Abstract: Objective: Tympanostomy tube insertion is the most common pediatric surgery, but it typically requires general anesthesia. To facilitate in-office tube placement without general anesthesia, two complementary technologies have recently been developed comprising an iontophoresis system for delivering local anesthesia and an integrated tube delivery system. The purpose of this study was to evaluate behavioral support techniques used during a clinical study of the new technology for pediatric in-office tube placement without general anesthesia or physical restraints. Methods: As part of an IRB-approved, prospective, nine-center clinical study, pediatric patients requiring tube insertion underwent in-office treatment using the new procedure. The behavior management techniques included preparation, distraction, coaching, and reinforcement for cooperation. The entire procedure was videotaped and two independent coders used the validated FLACC (Face, Legs, Activity, Cry, Consolability) scale to code behavioral distress across five procedural phases. Results: Seventy pediatric patients aged 8 months to 17 years ( M  = 7.0 years; 51% female) were enrolled in the study and 68 had video recordings available for analysis. Of the 68 recordings analyzed, 63 patients completed the procedure and had tubes placed without sedation. Mean FLACC scores ranged from 0.05 to 2.38 ( M  = 1.25, SD = 0.82) and median FLACC scores ranged from 0 to 1 (Mdn  =  0, IQR = 0.05), which indicate "mild" distress. During iontophoresis, eardrum tap (anesthesia assessment), and tube delivery, older children displayed lower distress and girls had higher FLACC scores during the eardrum tap procedural phase. Conclusion: When combined with the evidence-based behavioral techniques, office-based local anesthesia and tube delivery resulted in minimal distress, suggesting that the new procedure may be a viable method of conducting tympanostomy tube placement in children without having to use general anesthesia. Clinicaltrials.gov identifier:NCT01496287 .